Wheel set run profile renewing method effectiveness estimation - Somov, Dmitrij; Bazaras, Žilvinas; Žukauskaite, Orinta (Univerzita Pardubice, 2010)
At all the repair enterprises, despite decreased rim wear-off resistance, after every grinding only geometry wheel profile parameters are renewed. Exploit wheel rim work edge decrease tendency is noticed what induces acquiring new wheels. This is related to considerable axle load and train speed increase and also because of wheel work edge repair method imperfection.
Keywords: wheel rim; wheel rim metal; thermal wheel profile processing; restoration